1998
DOI: 10.2190/mb9b-6tvc-2vmd-xab5
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Habits among High School Boys in the United Arab Emirates

Abstract: This study reports on findings of a survey of smoking behavior and attitudes of approximately 1500 public secondary school boys in three major cities of the United Arab Emirates (UAE), one of the most rapidly developing societies in the world. Using an adaptation of the World Health Organizations Smoking Questionnaire and a multi-stage cluster sample of public schools and classes, the survey determined that 18.9 percent were current smokers and another 28.2 percent had smoking experience but were not active at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…This review shows that the prevalence rate of smoking in Yemen, Palestine, Bahrain, Jordan, Tunisia, Egypt, UAE and KSA had a higher prevalence which were observed among males more than females (36.3% vs 28.0%), (52.7% vs 16.5%), (27.0% vs 4.2%), (54.3% vs 11.1% and 56.9% vs 11.4%),(38.4% vs 3.4%), (61.2% vs 18.9%), (33.0% vs 3.9%) and (32.7% vs5.9%) respectively (Nasser and Zhang, 2019;Musmar, 2012;Alzayani and Hamadeh, 2015;Obeidat et al, 2014;Khader and Alsadi, 2008;Maatouk et al, 2013;Khan et al, 2012;Mandil et al, 2005) and (Mandil et al, 2011) (Table1). This is compatible with many studies conducted in Mediterranean and Arab countries that indicates a significantly higher prevalence of smoking among males, which may be due to the social acceptability of the smoking habit among males (Metintaş et al, 1998;Haddad and Malak, 2002;Hasim, 2000;Melani et al, 2000;Bener et al, 1999). A literature review of smoking in KSA (Bassiouny, 2009) confirms that smoking was reported to be higher among males compared to females, regardless of the age group of study (school children, university students, adults).…”
Section: Discussionsupporting
confidence: 90%
“…This review shows that the prevalence rate of smoking in Yemen, Palestine, Bahrain, Jordan, Tunisia, Egypt, UAE and KSA had a higher prevalence which were observed among males more than females (36.3% vs 28.0%), (52.7% vs 16.5%), (27.0% vs 4.2%), (54.3% vs 11.1% and 56.9% vs 11.4%),(38.4% vs 3.4%), (61.2% vs 18.9%), (33.0% vs 3.9%) and (32.7% vs5.9%) respectively (Nasser and Zhang, 2019;Musmar, 2012;Alzayani and Hamadeh, 2015;Obeidat et al, 2014;Khader and Alsadi, 2008;Maatouk et al, 2013;Khan et al, 2012;Mandil et al, 2005) and (Mandil et al, 2011) (Table1). This is compatible with many studies conducted in Mediterranean and Arab countries that indicates a significantly higher prevalence of smoking among males, which may be due to the social acceptability of the smoking habit among males (Metintaş et al, 1998;Haddad and Malak, 2002;Hasim, 2000;Melani et al, 2000;Bener et al, 1999). A literature review of smoking in KSA (Bassiouny, 2009) confirms that smoking was reported to be higher among males compared to females, regardless of the age group of study (school children, university students, adults).…”
Section: Discussionsupporting
confidence: 90%
“…[26,27] The fact that current smoking is associated with best friend being a smoker could either suggest peer influence in initiating smoking or that smokers are likely to be friend of other smokers. [28] In this study as in other studies, [26,[29][30][31][32] there was an a association between age, male sex, family history of smoking, low educational level of parents, high economic level, and the amount of pocket money and smoking. Having a parent who is a smoker was associated with being a current smoker.…”
Section: Discussionsupporting
confidence: 81%
“…As expected, more male family members than female family members smoked water pipes in the home for both Arab Americans and non–Arab Americans. These high percentages of home exposure are a concern for youth because of the hazards associated with secondhand smoke exposure34 as well as the increased likelihood of becoming a tobacco user when family members smoke 35,36. While the percentages of non–Arab-American family members smoking water pipes in the home were low, it calls for further investigation with adults as well as youth among all racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%